What fairness means to crime victims: a social psychological perspective - Wemmers, Jo-Anne M. (Applied psychology in criminal justice, 2006)
While victims are often considered the forgotten party in the criminal justice system, restorative justice has emerged as a new approach that includes victims by making them part of the legal response to crime. Based on interviews with victims who were invited to participate in a victim-offender mediation program, the present study examines victims' procedural justice judgements. The theoretical framework for the study is based on the procedural justice theory (Lind & Tyler, 1988; Tyler, 2003). Victims seek more than merely an opportunity to express themselves. It is not enough that victims can make demands; they also want their voices to be heard. This paper closes with a discussion of the implications of the findings.